UMP publisher organized e-book and Ghani Format Seminar - Shalfarina, Shahriman (Penerbit UMP, 2014)
Kuantan: More than 100 first-year degree undergraduates attended a learning seminar on the using of Ghani Format and a briefing on e-Book organised by UMP Publisher at Astaka Hall which was held early of the month.